Conformational dependence of the UV absorption spectrum of CH3CH2CHOO following excitation to the B1A′ state: research paper - Nikoobakht, Behnam; Köppel, Horst (Chemical physics letters, 2023)
The spectroscopy and dynamics of the Criegee intermediate CH3CH2CHOO following UV excitation to the B state are studied theoretically. We compute separately the UV absorption spectra for the syn- and anti- conformers of CH3CH2CHOO, based on potential energy surfaces for the excited states obtained by using multireference electronic wave function and a quantum dynamical approach for the nuclear motion. Our calculation shows a clear separation between the spectra of the two conformers as observed experimentally for the other Criegee intermediate, i.e., syn- and anti- CH3CHOO. Two interacting electronic states and three nuclear degrees of freedom (OO and CO stretching modes as well as COO bending modes) are considered in the dynamical treatment. The role of vibronic coupling and conformational dependence of the cumulative spectrum are investigated in more detail.